Learning Microsoft Word 2011 for the Mac - Vaccaro, Guy (InfiniteSkills, 2011)
"In this computer based training course, expert author Guy Vaccaro teaches you how to get the most out of Word 2011 for the Mac. Presented in the form of various projects, you will learn by actually creating useful documents. Starting with a letter, you learn about setting up your document. You will learn about inserting date and time, spell checking, and saving your document safely. You will then proceed in the video training to creating a mail merge, an email campaign, creating a manual, and your own templates. Throughout you will learn about formatting your document, inserting Table of Contents, adding images, styling text, and much, much more. By the completion of this Microsoft Word 2011 computer based video tutorial, you will be completely comfortable in creating professional looking documents in this extremely popular software program. Working files are included, to allow you to work with the same materials that the author is using in the training."--Resource desciption page.